PENGARUH KONFIGURASI DAN KEDALAMAN PENANAMAN KONDUKTOR TERHADAP RESISTANS PENTANAHAN GARDU INDUK TEGANGAN EKSTRA TINGGI (GITET) 500 KV UNGARAN - Ahmad Riyanda Saputra; Muhamad Haddin; Agus Adhi Nugroho (PSTE UNIMUS, 2018)
The earthing system is one of the most important parts of protection equipment in the substation. In the event of more voltage disturbance, with the earth system causing the current disturbance quickly flowed into the ground. the grounding resistance of a good substation inaccordance with the standard is ≤ 1ohm. The values can be affected by some parameters of the earth system such as the number of parallel conductors, the depth of the conductor cultivation, the distancebetween the parallel conductor, the ground area and the ground type resistance.Test results on GITET 500 kV Ungaran get the value of grounding resistance of 0.22 Ω, then for the actual touch voltagevalue of 698.03 V and the actual step voltage of 369.84 V. However, at the time of modification of grounding parameters, the test results obtained for the highest value of grounding resistance of 0.3400 Ω and the lowest value of 0.2212 Ω, then for the highest value at the actual touch voltage of 2582.40 V from the influence of the number of conductors parallel and the depth of the conductor planting and the lowest value of 893.73 V, while at the actual step voltage the highest value of 1093.60 V and thelowest value of 149.65 V, then for the influence of the number of parallel conductors and the distance between the parallel conductors at the actual touch voltage the highest value of 1634.10 V and the lowest value of 888.56 V, while the actual step voltage is the highest value of 1542.23 V and the lowest value of 447.17 V. Keywords: Grounding System, Effect of Resistance Ground